Tumour mutational burden using a targeted panel approach for comprehensive tumour profiling focusing on colorectal cancer - Rodney J. Scott; Andrew Ziolkowski; David Mossman; Michael Hipwell (Hereditary Cancer in Clinical Practice)
Abstract There is an increasing recognition that comprehensive tumour profiling (CTP) represents an important adjunct to the diagnosis of malignancy providing not only an assessment of how many mutations there are in any given tumour which reflects the probability of immune checkpoint inhibitor success, but also which mutations are associated with targeted therapies, a signature that reflects environmental insult and potentially the identification of cancers of unknown origin. This short review describes an approach to assaying tumour mutational burden (TMB), what the difficulties are in the assessment of the TMB and what it can be applied to in regards to improving patient outcomes. A final section of the review delves into some examples of colorectal cancer studies that identify findings that suggest there remains much to learn about tumour development.